ANALYSIS OF GOVERNMENT AND NON-GOVERNMENT INVESTMENT IN TPASR PROBOLINGGO DEVELOPMENT - Irwanto, Aditya; Oetomo, Wateno; Koespiadi (Transpublika Publisher, 2024)
Waste management is a pressing issue in Probolinggo Regency and City, necessitating swift action to mitigate environmental impacts. The construction of the Probolinggo Regional Waste Landfill (TPA) aims to address this challenge through cross-regional sanitation services. Proper financing is crucial for successful infrastructure development, and this study compares government budget (APBN/APBD) and non-government (regional loans) financing schemes. Utilizing a quantitative approach with primary and secondary data, the analysis indicates the viability of both financing options. Government-sourced investment shows an NPV of Rp 431,148,007,790, IRR 40.55%, BCR 1.07, and a 3-year payback period. Meanwhile, non-government or regional loans exhibit an NPV of Rp 110,115,495,905, IRR 9.03%, BCR 1.3, and a 9-year payback period. The decision-making process, weighing financial and non-financial criteria, favors regional loans/loans as the preferred financing scheme for the Probolinggo TPASR project. This research emphasizes the importance of a well-selected financing scheme to ensure the success and sustainability of the Probolinggo Regional Waste Landfill infrastructure.